A Web-based Fuzzy Inference System Based Tool for Cardiovascular Disease Risk Assessment - Yunda, Leonardo; Pacheco, David; Millan, Jorge (Revista Nova publicación científica en ciencias biomédicas, 2015)
Developing a Web-based Fuzzy Inference Tool for cardiovascular risk assessment. The tool uses evidence-based medicine inference rules for membership classification. Methods. The system framework allows adding variables such as gender, age, weight, height, medication intake, and blood pressure, with various types of membership functions based on classification rules. Results. By inputting patient clinical data, the tool allows health professionals to obtain a prediction of cardiovascular risk. The tool can also be later used to predict other types of risks including cognitive and physical disease conditions.